Effects of Shifting Saving Patterns on Interest Rates and Economic Activity - Friedman, Benjamin M. (Journal of Finance, 1982)
Individuals in the United States consistently do most of their saving through financial intermediaries, but over time there have been and continue to be major shifts in people's reliance on specific kinds of intermediary institutions. In recent years, for example, individual savers have relied progressively more on pensions and thrift institutions and progressively less on life insurance companies. Moreover, legislative and regulatory actions currently under discussion would further alter the pattern of individuals' saving flows. This paper assesses the potential effects on interest rates, and via interest rates (and asset prices and yields more generally) on nonfinancial economic activity, of four specific shifts in saving behavior: additional pension contributions financed by individuals, additional pension contributions financed by businesses, additional purchases of life insurance by individuals, and additional deposits in thrift institutions by individuals. The paper's results indicate that such shifts, in plausible magnitudes, would have significant effects not only on interest rates and asset-liability flows but also on both the level and the composition of nonfinancial economic activity. In particular, although the specific effects differ from one shift to another, each would disproportionately stimulate capital formation in comparison to other forms of spending.